1987
DOI: 10.1002/jso.2930360210
|View full text |Cite
|
Sign up to set email alerts
|

Mucoepidermoid carcinoma arising from a preexisting cyst of the liver

Abstract: A case of mucoepidermoid carcinoma of the liver of a 46-year-old female is described. The resected mass from the left lobe of the liver measured 3 X 3 X 2 cm. The cut surface showed a well demarcated white, round shape, and a cystic formation measuring 1.8 X 1.4 cm was present in the center of the mass. Microscopically, the mass showed high-grade-type mucoepidermoid carcinoma, which consisted of squamous cells, mucus-producing cells, and glandular cells. The cystic wall was lined with apparently benign glandul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0
1

Year Published

1994
1994
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 7 publications
0
35
0
1
Order By: Relevance
“…Some authors observed the remarkable neoplastic transformation of the normal duct lining epithelium, which suggested a possible of bile duct origination [16]. Some authors proposed that mucoepidermoid carcinoma of the liver might originate from a congenital cyst because the main tumors were located in the vicinity of multiple seromucinous cysts lined with columnar, cuboidal glandular epithelium with no connection to the biliary system and no bile content [8,11]. The electron micrographs revealed tonofilaments and confirmed the squamous nature of the tumor cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors observed the remarkable neoplastic transformation of the normal duct lining epithelium, which suggested a possible of bile duct origination [16]. Some authors proposed that mucoepidermoid carcinoma of the liver might originate from a congenital cyst because the main tumors were located in the vicinity of multiple seromucinous cysts lined with columnar, cuboidal glandular epithelium with no connection to the biliary system and no bile content [8,11]. The electron micrographs revealed tonofilaments and confirmed the squamous nature of the tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Because of its relative rarity in liver, its etiology has not yet been elucidated. Terminal intrahepatic bile ducts or biliary congenital cysts have been proposed as a possible origin [5,7,8,11]. Histologically, mucoepidermoid carcinoma is characterized by squamoid (epidermoid), mucus producing and cells of intermediate type.…”
Section: Introductionmentioning
confidence: 99%
“…It has been also reported that MEC may arise from preexisting congenital cysts [6, 7] in which the epithelium may transform into pluripotent intermediate cells, capable of differentiating into both mucin-secreting and squamous cells [6]. Similarly, Onoda et al demonstrated by electron microscopy that undifferentiated cells of the pancreatic duct showed multipotency [3].…”
Section: Discussionmentioning
confidence: 99%
“…1,2,[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] The preoperative diagnosis was extremely difficult, with only three patients correctly diagnosed by aspiration cytology.…”
Section: Discussionmentioning
confidence: 99%